2002
DOI: 10.1002/mrdd.10027
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathology of Rett syndrome

Abstract: Rett Syndrome is unlike any other pediatric neurologic disease, and its clinical-pathologic correlation can not be defined with standard histology techniques. Based on hypotheses suggested by careful clinical observations, the nervous system of the Rett child has been explored utilizing morphometry, golgi preparations, computerized tomography, magnetic resonance imaging, chemistry, immunocytochemistry, autoradiography, and molecular biologic techniques. From these many perspectives we conclude that Rett syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(42 citation statements)
references
References 71 publications
2
36
0
3
Order By: Relevance
“…Specifically there may be small dendritic trees in pyramidal neurones of layers III and IV of the cortex of frontal and temporal lobes and immaturity of cardiorespiratory neurones in brain stem centres suggesting failure of growth of axonodendritic connections composing the neuropil. 3,18,19 Studies have also demonstrated reduced levels of neurotransmitters, including serotonin, noradrenaline, dopamine and choline acetyltransferase. 4 In the reported case there was microcephaly with essentially non-specific neurological findings that may have been secondary to seizure activity.…”
Section: Discussionmentioning
confidence: 96%
“…Specifically there may be small dendritic trees in pyramidal neurones of layers III and IV of the cortex of frontal and temporal lobes and immaturity of cardiorespiratory neurones in brain stem centres suggesting failure of growth of axonodendritic connections composing the neuropil. 3,18,19 Studies have also demonstrated reduced levels of neurotransmitters, including serotonin, noradrenaline, dopamine and choline acetyltransferase. 4 In the reported case there was microcephaly with essentially non-specific neurological findings that may have been secondary to seizure activity.…”
Section: Discussionmentioning
confidence: 96%
“…The neuropathology of Rett syndrome has been extensively reviewed on several occasions (Jellinger and Seitelberger 1986;Armstrong 2001Armstrong , 2002. As far as bioaminergic systems are concerned, it is interesting to note that one of the first post-mortem reports described a marked reduction in dopamine, norepinephrine, serotonin and the 5-HIAA and HVA metabolites (Riederer et al 1986).…”
Section: Neuropathologymentioning
confidence: 98%
“…An inspection of the primary structure of CDKL5 revealed the presence of a stretch of amino acids from 836 to 845 (LKSLRKLLHL) sharing high homology with the consensus NES (LX (2,3) [LIVFM]X (2,3) …”
Section: Els C G and K O)mentioning
confidence: 99%
“…Rett syndrome (RTT, 3 OMIM 312750) is an X-linked neurodevelopmental disorder that occurs almost exclusively in girls with an incidence of 1:10,000 female births. Patients affected with classic RTT are usually born healthy and start manifesting symptoms after an apparently normal period of development lasting 6 -18 months (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation